2012
DOI: 10.1063/1.4716190
|View full text |Cite
|
Sign up to set email alerts
|

A master-equation approach to simulate kinetic traps during directed self-assembly

Abstract: Robust directed self-assembly of non-periodic nanoscale structures is a key process that would enable various technological breakthroughs. The dynamic evolution of directed self-assemblies towards structures with desired geometries is governed by the rugged potential energy surface of nanoscale systems, potentially leading the system to kinetic traps. To study such phenomena and to set the framework for the directed self-assembly of nanoparticles towards structures with desired geometries, the development of a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
25
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
5
3

Relationship

3
5

Authors

Journals

citations
Cited by 17 publications
(25 citation statements)
references
References 34 publications
0
25
0
Order By: Relevance
“…The probability of observing the nanoparticles in a particular configuration as a function of time is given by a master equation: 1,5 …”
Section: Introductionmentioning
confidence: 99%
“…The probability of observing the nanoparticles in a particular configuration as a function of time is given by a master equation: 1,5 …”
Section: Introductionmentioning
confidence: 99%
“…The control scheme in this paper was primarily developed for use in directed self-assembly of nanoparticles [11]- [19]. Self-assembly is the process of forming an ordered structure from initially disordered components that only interact locally, without external direction.…”
Section: Introductionmentioning
confidence: 99%
“…In many applications, however, nanostructures with specific nonperiodic geometries are required. To address the need for fabrication of nanostructures with specific geometries, researchers proposed to direct the self-assembly process towards the desired geometry using external controls [11]- [19].…”
Section: Introductionmentioning
confidence: 99%
“…Local manipulation of fields (e.g., temperature, concentration, pH, electric field, and magnetic field) has been shown in simulations to drive the system toward a particular desired configuration with a high probability [52,53,55]. Methods for qualitative and quantitative shaping of the energy landscape through manipulation of these fields were reviewed in Section 3.2.…”
Section: Outlook For Future Researchmentioning
confidence: 99%
“…This no-measurements situation naturally gives rise to stochastic models for describing the system dynamics such as (1) and (3). In [55], a Master equation model was used in conjunction with the aforementioned methods of [52,53]. It is shown that open-loop control schemes can drive the self-assembly of the system (in simulations) to a targeted configuration with high probability.…”
Section: Open-loop Controlmentioning
confidence: 99%